Interactive Multimedia Publication System for Building Web Services - Vardanyan, Ruben (Mathematical Problems of Computer Science, 2021)
Interactive Multimedia Publications are of high importance in many application areas including education, training and entertainment. It explains the high demand in web services providing the effective tools of authoring and interacting with this kind of publications. This paper is aimed to present the Interactive Multimedia Publication System, which can be used for building the above mentioned web services and having capabilities significantly exceeding those of the existing ones. The paper gives the high-level architectural view of the systems and outlines the communication protocol used between the client and server components of the system.